2018
DOI: 10.3727/096504018x15172227703244
|View full text |Cite
|
Sign up to set email alerts
|

B7-Homolog 4 Promotes Epithelial‐Mesenchymal Transition and Invasion of Bladder Cancer Cells via Activation of Nuclear Factor-κB

Abstract: B7-homolog 4 (B7-H4), a member of the B7 family of costimulatory molecules, has been reported to be upregulated in urothelial cell carcinoma. This study was conducted to explore the biological role of B7-H4 in the aggressiveness of bladder cancer and the associated molecular mechanism. We found that the mRNA and protein levels of B7-H4 were significantly greater in bladder cancer cell lines than in SV-HUC-1 (normal human urothelial cells). Overexpression of B7-H4 significantly promoted bladder cancer cell migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…For example, B7-H4 upregulation induces immune escape of lung cancer [ 42 ] and non-small cell lung cancer cells [ 43 ] through MEK/ERK and PD-1/Stat3 signaling pathways. B7-H4 overexpression promotes the metastasis of bladder cancer cells through Nuclear Factor-kappa B signaling [ 44 ]. However, the mechanism by which B7-H4 promotes the migration of CRC cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, B7-H4 upregulation induces immune escape of lung cancer [ 42 ] and non-small cell lung cancer cells [ 43 ] through MEK/ERK and PD-1/Stat3 signaling pathways. B7-H4 overexpression promotes the metastasis of bladder cancer cells through Nuclear Factor-kappa B signaling [ 44 ]. However, the mechanism by which B7-H4 promotes the migration of CRC cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, PD-L1 has been confirmed to be an important mediator of EMT in certain human cancer tissues, such as lung cancer, colorectal cancer, esophageal cancer, and head and neck cancer [28, 4042]. Moreover, other members such as B7-H3 and B7-H4, have also been suggested to promote EMT of cancer cells during cancer progression [4345].…”
Section: Discussionmentioning
confidence: 99%
“…B7-H3 and B7-H4 (VTCN1) belong to a family of immune modulators that includes PD-L1 (B7-H1) and are regarded as a promising molecular target for immunocheckpoint therapy [24]. In fact, many preclinical studies reported the possible effectiveness of B7-H3- or B7-H4-targeting antibody, among the B7 family, in the treatment of cancers [25,26,27,28,29]. Furthermore, since we would like to elevate our study to translational research, we focused on B7-H3 and B7-H4, which are currently being tested in a clinical trial [30,31,32].…”
Section: Discussionmentioning
confidence: 99%